2019
DOI: 10.1016/j.echo.2018.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Right Ventricular Contractile Reserve Is Impaired in Children and Adolescents With Repaired Tetralogy of Fallot: An Exercise Strain Imaging Study

Abstract: Background: Pulmonary insufficiency (PI) and right ventricular (RV) dysfunction are long-term complications in rTOF. We sought to investigate RV contractile reserve and changes in PI that occur during exercise in patients with repaired tetralogy of Fallot (rTOF) and the association of these changes with exercise performance using stress echocardiography. Methods: Subjects with rTOF (n = 32) and healthy controls (n=10) were prospectively enrolled and underwent rest and peak exercise echocardiograms during sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 46 publications
0
21
0
Order By: Relevance
“…Normal resting RV longitudinal function may therefore be falsely reassuring in the context of RV dilatation. Other studies have utilised a variety of exercise measurements, including TAPSE, RV fractional area change, and RV longitudinal strain, to demonstrate impaired RV functional reserve in tetralogy of Fallot repair patients with residual PR ( 55 , 56 ). Further studies such as these are needed to help refine surgical criteria, by identifying patients that will benefit from earlier intervention due to occult RV dysfunction seen only during stress, or conversely those with irreversible RV damage in whom operative risk might outweigh any potential gains.…”
Section: Stress Echocardiographymentioning
confidence: 99%
“…Normal resting RV longitudinal function may therefore be falsely reassuring in the context of RV dilatation. Other studies have utilised a variety of exercise measurements, including TAPSE, RV fractional area change, and RV longitudinal strain, to demonstrate impaired RV functional reserve in tetralogy of Fallot repair patients with residual PR ( 55 , 56 ). Further studies such as these are needed to help refine surgical criteria, by identifying patients that will benefit from earlier intervention due to occult RV dysfunction seen only during stress, or conversely those with irreversible RV damage in whom operative risk might outweigh any potential gains.…”
Section: Stress Echocardiographymentioning
confidence: 99%
“…Previous studies assessing RV functional reserve have predominantly looked at the relative change in peak strain from rest-to-exercise. 24,25 Vitarelli et al identified ΔSL as the most accurate parameter to identify subjects with ARVC. 12 However, in these studies cardiac function was already impaired in the rested state, as opposed to our cohort in which RV function was ostensibly normal at rest.…”
Section: Deformation Imaging In Arrhythmogenic Rv Pathologymentioning
confidence: 99%
“…While LS A4C and CS mid are more limited components of strain, published pediatric reference values for calculation of standard deviation scores (SDS) by body surface area (BSA) are available, 24 and there are also data to suggest they are good approximations of global measures based on averages of three views 25 . Strain measurements were analyzed offline using Image Arena Version 4.6 (TomTec Imaging Systems) by an experienced research sonographer (YW) with proven intra‐observer reliability 26,27 …”
Section: Methodsmentioning
confidence: 99%
“…with proven intra-observer reliability. 26,27 Standard measures of LV systolic function were assessed, including ejection fraction (LVEF) and shortening fraction (LVSF). We also assessed measures of LV diastolic function, including mitral E/A ratio (peak early over peak late diastolic filling velocity), septal and lateral e′ (early diastolic mitral annular tissue velocity), E/e′ ratio (peak early diastolic filling velocity over early diastolic mitral annular tissue velocity), isovolumetric relaxation time (IVRT), deceleration time (DT), and left atrial volume index (LAVI).…”
Section: College Of Rheumatology or Systemic Lupus Internationalmentioning
confidence: 99%